PENGARUH SIZE PERUSAHAAN, KEPEMILIKAN SAHAM PUBLIK, KEPEMILIKAN SAHAM ASING, DAN PROFITABILITAS PERUSAHAAN TERHADAP PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY (CSR) PADA PERUSAHAAN FOOD AND BEVERAGES YANG TERDAFTAR DI BEI PADA TAHUN 2010-2013 - Rahmayanty, Sri; Tanjung, Amries Rusli; Susilatri, Susilatri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This study aimed to determine the effect of firm size, public ownership, foreign ownership, and profitability of the company on the disclosure of Corporate Social Responsibility (CSR) in the food and beverage companies listed on Indonesian Stock Exchange in 2010-2013. Samples are 16 companies that are determined by purposive sampling. The instrument used was a checklist item CSR disclosure. Data was analyzed using multiple linear regression method (multiple regression) with SPSS version 17.0. The results of the study showed that public ownership, and profitability significantly influence CSR disclosure. While the firm size and foreign ownership does not significant effect on CSR disclosure.Keywords : Corporate social responsibility, firm size, public ownership, foreign ownership, and the profitability of the company.